2017
DOI: 10.1016/j.freeradbiomed.2016.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-induced mitochondrial dysfunction is associated with impaired cognitive function in rats

Abstract: Purpose Chemotherapy-related cognitive impairment (CRCI) is commonly reported following the administration of chemotherapeutic agents and comprises a wide variety of neurological problems. No effective treatments for CRCI are currently available. Here we examined the mechanisms involving cisplatin-induced hippocampal damage following cisplatin administration in a rat model and in cultured rat hippocampal neurons and neural stem/progenitor cells (NSCs). We also assessed the protective effects of the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 63 publications
1
93
0
2
Order By: Relevance
“…It is widely assumed that conventional chemotherapies do not cross the brain blood barrier (BBB). However, recent data reveal that agents such as doxorubicin, cyclophosphamide and cisplatin, do, in fact, cross the BBB, and thus may have effects on the decreased mitochondrial function, increase the oxidative stress and lead to morphological changes in the brain and consequently to neurophysiological dysfunction (Ahles & Saykin, ; Kitamura et al , ; Lomeli et al , ). Our findings revealed that HLS who received fewer chemotherapy cycles had better neurocognitive performance and were consistent with previously published data (Baudino et al , ), supporting these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely assumed that conventional chemotherapies do not cross the brain blood barrier (BBB). However, recent data reveal that agents such as doxorubicin, cyclophosphamide and cisplatin, do, in fact, cross the BBB, and thus may have effects on the decreased mitochondrial function, increase the oxidative stress and lead to morphological changes in the brain and consequently to neurophysiological dysfunction (Ahles & Saykin, ; Kitamura et al , ; Lomeli et al , ). Our findings revealed that HLS who received fewer chemotherapy cycles had better neurocognitive performance and were consistent with previously published data (Baudino et al , ), supporting these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…These adverse effects include neurotoxicity, hepatotoxicity, nephrotoxicity, ototoxicity, myelosuppression, gastrointestinal toxicity, and cardiotoxicity. Common neurological adverse effects are cognitive deficits, disorientation, visual perception, and hearing disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, cognitive decline after chemotherapy is not specific to thioTEPA. Many different chemotherapy drugs are associated with cognitive decline (Moore, )—doxorubicin, cyclophosphamide, cisplatin, and 5‐fluorouracil (5‐Fu) are all associated with cognitive dysfunction (Kitamura et al, ; Lomeli, Di, Czerniawski, Guzowski, & Bota, ; Lyons, ElBeltagy, Bennett, & Wigmore, ). Previously, we showed that 5‐Fu decreases dendritic arborization in the mouse hippocampus (Groves et al, ).…”
Section: Discussionmentioning
confidence: 99%